Competitive selection of school principals: a case study of an innovation in Brazil - de Mello, Guiomar (International Institute for Educational Planning ParisFR, 1993)
Provides a case study of Minas Gerais, one of the most significant states in economic and political terms. Looks at the innovation and its context; its origin and development; the results of the innovation and its development. Presents conclusions and recommendations.